A comparison of routine diabetes screening by sexual orientation in US adults. (1st February 2021) - Tran, Phoebe; Tran, Lam; Tran, Liem
Abstract: Little is known about routine diabetes screening levels (test for high blood glucose or diabetes every three years) in US individuals who identify as lesbian, gay or bisexual (LGB) despite a high risk of diabetes in these groups. We compared routine diabetes screening levels between US adult LGBs and heterosexuals who belonged to either of the two American Diabetes Association's (ADA) recommended diabetes screening groups (age <45 years and body mass index (BMI) ≥25, age ≥45 years). Sexual orientation, diabetes screening and sociodemographic/diabetes risk factor information was collected from the 2015 and 2017 Behavioral Risk Factor Surveillance System surveys. We calculated the unadjusted prevalence of diabetes screening in LGBs and heterosexuals for both ADA screening groups. Logistic regression modelling was used to obtain adjusted diabetes screening estimates by sexual orientation. LGBs had slightly higher unadjusted diabetes screening prevalences (age <45 years and BMI ≥25: 53.2%; age ≥45 years: 72.3%) compared to heterosexuals (age <45 years and BMI ≥25: 51.7%; age ≥45 years: 69.9%) for both ADA recommended screening groups. Irrespective of sexual orientation, diabetes screening prevalence was considerably lower in the younger ADA screening group with around 50% of individuals who should be screened not receiving screening. After adjustment for sociodemographic/diabetes risk factors, LGBs and heterosexuals had similar odds of diabetes screening in the age <45 years and BMI ≥25 (odds ratio [OR]: 0.98, 95% confidence interval [CI]: 0.80–1.21) and age ≥45 years (OR: 1.11, 95% CI: 0.91–1.35) groups. As a result of not receiving routine diabetes screening, more than 100, 000 LGB individuals at high risk of developing diabetes face potential delays in diabetes diagnosis and treatment as well as increased future diabetes complications. Copyright © 2021 John Wiley & Sons.